2005
DOI: 10.1002/adfm.200500211
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable, Efficient Polymer Solar Cells with Nanoscale Control of the Interpenetrating Network Morphology

Abstract: By applying the specific fabrication conditions summarized in the Experimental section and post‐production annealing at 150 °C, polymer solar cells with power‐conversion efficiency approaching 5 % are demonstrated. These devices exhibit remarkable thermal stability. We attribute the improved performance to changes in the bulk heterojunction material induced by thermal annealing. The improved nanoscale morphology, the increased crystallinity of the semiconducting polymer, and the improved contact to the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

97
3,650
14
20

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 4,508 publications
(3,815 citation statements)
references
References 29 publications
97
3,650
14
20
Order By: Relevance
“…A substantial improvement in the PCE of P3HT:PCBM based solar cells has been obtained by thermal annealing at around 140 1C, and the favourable influence of annealing on blend film microstructure and solar cell performance is well documented. [50][51][52][53] The mechanism by which current density and PCE increase upon thermal annealing in P3HT:PCBM is not known precisely but it is believed to involve increased optical absorption and improved charge transport, both due to polymer crystallization, as well as improved charge pair separation efficiency, due to optimized phase segregation. Some of the literature is reviewed below.…”
Section: Thermal Annealingmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial improvement in the PCE of P3HT:PCBM based solar cells has been obtained by thermal annealing at around 140 1C, and the favourable influence of annealing on blend film microstructure and solar cell performance is well documented. [50][51][52][53] The mechanism by which current density and PCE increase upon thermal annealing in P3HT:PCBM is not known precisely but it is believed to involve increased optical absorption and improved charge transport, both due to polymer crystallization, as well as improved charge pair separation efficiency, due to optimized phase segregation. Some of the literature is reviewed below.…”
Section: Thermal Annealingmentioning
confidence: 99%
“…60 AFM studies revealed that films cast from more concentrated solutions or solutions with smaller P3HT:PCBM ratios exhibited ''overgrown'' PCBM crystals after high-temperature annealing, leading to degradation of the morphology and poor device performance. 52 A study using differential thermal calorimetry has shown that the P3HT:PCBM binary possesses a eutectic phase behaviour, such that the polymer:fullerene interface area is maximized and the domain size minimized at a blend composition of about 35% PCBM by weight. 61 The higher PCBM content required for maximum efficiency is explained in terms of the need for sufficient PCBM to build up a sufficiently conducting network to achieve balanced charge mobility, in agreement with the ToF measurements cited above.…”
Section: Blend Compositionmentioning
confidence: 99%
“…The glancing angle X-ray diffraction (GAXRD) pattern, see Figure 4, of the completed device shows the presence of highly crystalline P3HT, where the peak at 2θ ) 5°corresponds to a P3HT interchain spacing associated with interdigitated alkyl chains. 46,47 Details of the device structure, and hence performance, are dependent on the device fabrication procedure. Consider as an illustration the incident photon to collected electron efficiency (IPCE) of three of the described P3HT/dyesensitized TiO 2 nanotube array devices, see Figure 5, with the P3HT solution (30 mg/mL, prepared using a 3:1 ratio of o-DCB and CB) applied in varying degrees of sample surface wetting as discussed in the preceding paragraph.…”
mentioning
confidence: 99%
“…Despite the improvements, the reported power conversion efficiencies remain lower than the current record. [31][32][33] Our devices are not fabricated under the exclusion of oxygen, which is known to limit the efficiency to the reported values. For example, domain 5 short circuit current drops by 58% after 10 h of air exposure, which is a common problem for organic thin film solar cells.…”
mentioning
confidence: 99%